Peningkatan Kualitas Pelayanan melalui Evaluasi Kepuasan Pasien di Unit Gawat Darurat dengan Pendekatan Net Promoter Score - Ngongoloy, Hesky Frengky; Astutik, Reni Yuli (Yayasan Inspirasi El Burhani, 2025)
Introduction: Patient satisfaction is a key indicator of healthcare quality. The Emergency Department (ED) of Prof. Dr. R. D. Kandou General Hospital, Manado, is one of the busiest hospital units, handling various critical cases. However, preliminary data indicated a NPS of –37%, suggesting that most patients were dissatisfied and unlikely to recommend the service. This prompted the need for a systematic evaluation and managerial intervention to improve the quality of nursing care and patient experience. Objective: To evaluate patient satisfaction with emergency department services at Prof. Dr. R. D. Kandou General Hospital using the NPS method, to identify key influencing factors, and to formulate improvement strategies based on nursing management principles. Method: This study applied a quantitative descriptive approach with an evaluative design. Data were collected from non-trauma ED patients using the NPS questionnaire. Root cause analysis was conducted using the Fishbone Diagram, problem prioritization with the USG (Urgency, Seriousness, Growth) method, and strategy development through SWOT analysis. Interventions included AIDET-based effective communication training and optimization of service flow and management in the emergency department. Result: Initial findings showed an NPS score of –37%. After implementing communication training and standard operating procedure (SOP) reinforcement, the NPS improved to +57%, with 70% promoters, 17% passives, and 13% detractors. This demonstrates a significant improvement in patient satisfaction and service quality following the managerial intervention. Conclusion: There was a substantial improvement in patient satisfaction after applying the NPS-based nursing management intervention. Effective communication, interprofessional collaboration, and data-driven quality evaluation significantly enhanced the quality of care in the emergency department. The NPS method proved to be a practical and reliable tool for measuring patient satisfaction and loyalty in hospital services.